Pendampingan Penyusunan Laporan Keuangan Bimbel di Kota Jambi: (Assistance in Preparing Financial Reports for Tutoring Schools in Jambi City) - Nerawaty , Netty; Rahayu, Sri; Tiswiyanti , Wiwik; Rahayu, Rahayu; Wulan B, Sylvia Kartika (Laboratorium Pembelajaran FKIP Universitas Jambi, 2025)
The purpose of this community service is to improve partners' understanding and skills in accounting and preparing financial reports. This community service was carried out at tutoring centers in Jambi City. There are still many tutoring centers that have not prepared financial reports properly. The method of implementing the community service is divided into several stages, namely the preliminary survey stage, the socialization stage, PPM implementation activities, activity evaluation and program sustainability. The community service was carried out at the Montessori Dandelion Tutoring House on Sunday, September 22, 2024. The results of the community service showed an increase in participants' understanding and skills in preparing financial reports properly. Abstrak.Tujuan pengabdian ini untuk meningkatkan pemahaman dan keterampilan mitra tentang akuntansi dan penyusunan laporan keuangan. Pengabdian ini dilaksanakan pada bimbel di kota jambi. Masih banyak bimbel yang belum menyususn laporan keuangan dengan baik. Metode pelaksanaan pengabdian dibagi dalam beberapa tahap yaitu tahap survei pendahuluan, tahap sosialisasi, kegiatan pelaksanaan PPM, evaluasi kegiatan dan keberlanjutan program. Pengabdian telah dilaksanakan di rumah Bimbel Montessori Dandelion pada hari Minggu tanggal 22 September 2024. Hasil pengabdian memperlihatkan adanya peningkatan pemahaman dan keterampilan peserta dalam penyusunan laporan keuangan dengan baik.